Enhancing Character Education and Students’ Positive Attitudes through Local Wisdom in the Era of Society 5.0: A Case Study in Vocational Schools - Arief Nurrahman; Sukirno; Ali Muhson; Marzuki (Indonesian Values and Character Education Journal, 2025)
In the era of Society 5.0, education is no longer sufficient to focus solely on the mastery of technical competencies but is required to foster students’ character development in a holistic and sustainable manner. A major challenge faced by vocational education lies in integrating meaningful and contextual character education without neglecting cultural identity within an adaptive curricular framework. This study aims to explore and analyze the role of local wisdom as a foundation for character education and its contribution to shaping students’ attitudes and civic values through the implementation of the Merdeka Curriculum. This research adopts a qualitative approach with a case study design. The research subjects include teachers and students in vocational schools. Data were collected through participatory observation, semi-structured interviews, and document analysis. Data analysis was conducted using the interactive model of Miles and Huberman, encompassing data condensation, data display, and conclusion drawing and verification. The findings indicate that the Pancasila Student Profile (P5) projects are implemented contextually through the integration of cultural practices and traditions into the learning process. This implementation contributes to the strengthening of national identity, environmental ethics, cultural pride, critical thinking, and students’ civic responsibility. The study concludes that character education based on local wisdom is effective in shaping vocational students’ character when supported by a flexible curriculum and contextual learning. The implications of this study emphasize the importance of institutional support and the strengthening of teachers’ capacity to realize culturally responsive and sustainable character education.